The use of entomopathogenic nematodes to control citus mealybug, Planococcus citri (Hemiptera: Pseudococcidae) on citrus in South Africa - Van Niekerk, Sonnica (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.